A LOW-TECH MiSSiON - Miller, Shannon McClintock; Hoena, Blake; Brown, Alan (North Mankato, Minnesota : STONE ARCH BOOKS, 2019)
When you have a problem, where can you go for answers? the library! when Eliza and her friends join Ms. Gillian, the specialist, on another adventure in makespace, they find themselves in ancient Scythia. Can they help Alexander the great win the battle of Jaxartes in 329 BCE?
t t
"A 4D book"--Back cover.
Ages 8-10
Keywords: Weapons, Ancient -- Juvenile literature; Catapult -- Juvenile literature; Makerspaces -- Juvenile literature; Weapons, Ancient -- Comic books, strips, etc